Factors Affecting Consumers’ Cashless Payment Behaviours Admist the COVID-19 Pandemic - Lu, Ming Pey; Kosim, Zunarni (Malaysian Communications and Multimedia Commission (MCMC), 2021)
The COVID-19 lockdown has caused many to shift to online shopping and increased the use of cashless payments. However, the statistics from Bank Negara Malaysia show that both the amounts of cash circulation and cash withdrawals from automatic teller machines (ATMs) in Malaysia still continues to rise. Hence, this study examines the influence of the COVID-19 pandemic on consumer behavioural intention to use cashless payments. This study applied the unified theory of acceptance and use of technology (UTAUT) model to examine the factors affecting consumers’ behaviour in adopting cashless payment with the COVID-19 pandemic acting as the moderating variable. The findings show that performance expectancy, effort expectancy, and social influence have significantly affected consumers’ behavioural intention to use cashless payments except for facilitating conditions. The findings demonstrate that COVID-19 has significantly moderated the relationship between four variables (performance expectancy, effort expectancy, social influence, and facilitating conditions) on the behavioural intention to use cashless payment. This study further shows that the majority of respondents will have a high propensity towards the use of cashless payments in the future and always try to use cashless as their primary payment method. In brief, the pandemic has switched consumers’ behaviour and accelerated the adoption of cashless payment in Malaysia. Practitioners and cashless payment providers can use these findings as a guide to encourage consumers to integrate cashless as their preferred means of payment. This change could help Malaysia successfully transform into a fully cashless society.